Observational/Hydrographic data of the South Atlantic Ocean published as LOD - Braun, Germán Alejandro; Lewis, Mirtha Noemi; Fillottrani, Pablo; Zárate, Marcos Daniel
RDF dataset of occurrences of Southern Elephant Seals (SES) Mirounga leonina (Linnaeus, 1758) in two environments (marine and coastal). The data constitutes hydrographic measurements of instrumented animals and observation data collected during census between 1990 and 2017. The data, coming from Peninsula Valdés (UNESCO World Heritage), is available for interdisciplinary studies of management and conservation of marine and coastal protected areas which demand reliable and updated data. Fil: Braun, Germán Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional del Comahue. Facultad de Informatica; Argentina Fil: Lewis, Mirtha Noemi. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Fillottrani, Pablo. Universidad Nacional del Sur. Departamento de Ciencias e Ingeniería de la Computación; Argentina Fil: Zárate, Marcos Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina